2019
DOI: 10.3390/md17010061
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fermented Fish Oil on Fine Particulate Matter-Induced Skin Aging

Abstract: Skin is exposed to various harmful environmental factors such as air pollution, which includes different types of particulate matter (PM). Atmospheric PM has harmful effects on humans through increasing the generation of reactive oxygen species (ROS), which have been reported to promote skin aging via the induction of matrix metalloproteinases (MMPs), which in turn can cause the degradation of collagen. In this study, we investigated the effect of fermented fish oil (FFO) derived from mackerel on fine PM (part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 30 publications
1
44
0
Order By: Relevance
“…In the present study, we proved that PM could induce MMP-2 and MMP-9 activity and expression in SCC4 and SCC25 cells. On the other hand, PM2.5 has been shown to induce MMP-2 and MMP-9 expression in human keratinocytes and cause skin aging [6]. Indeed, we also found that the levels of MMP-2 and MMP-9 in oral cancer cells or breast cancer cells are higher than in human gingival fibroblasts under the stimulation of PM ( Supplementary Fig.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…In the present study, we proved that PM could induce MMP-2 and MMP-9 activity and expression in SCC4 and SCC25 cells. On the other hand, PM2.5 has been shown to induce MMP-2 and MMP-9 expression in human keratinocytes and cause skin aging [6]. Indeed, we also found that the levels of MMP-2 and MMP-9 in oral cancer cells or breast cancer cells are higher than in human gingival fibroblasts under the stimulation of PM ( Supplementary Fig.…”
Section: Discussionsupporting
confidence: 59%
“…MMP-2 or MMP-9 has been shown to play an important role in regulating metastasis including oral cancer [5,7]. PM2.5 also has been shown to induce MMP-2 and MMP-9 expression in keratinocytes [6]. Therefore, reducing the expression of MMP-2 and MMP-9 or its upstream regulatory signaling pathways is essential for the treatment of malignant tumors.…”
Section: Ivyspringmentioning
confidence: 99%
“…The endoplasmic reticulum (ER) is responsible for most of the intracellular Ca 2+, and, as a result, changes in the cellular Ca 2+ -balance activate ER stress [196]. PM was shown to induce ER stress, as measured by increased levels of intracellular Ca 2+ [123,168,175,[184][185][186]. Additionally, the ER stress sensor proteins for unfolded or misfolded proteins, protein kinase-like ER kinase (PERK), inositol-requiring 1 alpha (IRE1α), and activating transcription factor 6 (ATF6) [197], were activated in vitro [123,175].…”
Section: Pm Triggers Exogenous and Endogenous Ros Formationmentioning
confidence: 99%
“…Skin serves as the protective barrier of the body and protects it from harmful agents, such as ultraviolet (UV) radiation, heat and microorganisms (1,2). damage to the skin tissue not only causes damage to the subcutaneous tissue, but also affects the internal balance of the body (3,4).…”
Section: Introductionmentioning
confidence: 99%